PENERAPAN PENGUATAN LITERASI DALAM PEMBELAJARAN AMANCALISTUNG PADA PENDIDIKAN ANAK SEKOLAH DASAR - Dwi Safitri, Elviana; Trisia Octavia, Oksha; Prasetyo, Erlangga; Feni, Rita (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Literacy and numeracy skills are basic abilities that children really need because they are essentially the basis for learning other sciences. This service aims to improve the basic literacy skills of elementary school students through the Safe Reading, Writing and Counting literacy strengthening program. This activity was carried out at SD Muhammadiyah 2 Bengkulu City involving lower grade students. The methods used include providing material, direct practice, and evaluation. The results of this service show a significant increase in students' reading, writing and numeracy skills after participating in the program. Apart from that, this service also increases understanding of reading and writing, and students become more active and enthusiastic in participating in learning. Apart from that, this program also succeeded in creating a fun and conducive learning atmosphere.